Cathodic nanoporous CNT functional interlayer as a performance and durability boosting agent for proton exchange membrane fuel cells to operable at 120 °C. (31st October 2022) - Kwon, Obeen; Kim, Jaeyeon; Yoo, Hongnyoung; Choi, Heesoo; Cha, Hyeonjin; Kim, Gyosik; Kim, Hyeok; Jeong, Seokhun; Im, Dasom; Jeong, Youngjin; Park, Taehyun
Abstract: In proton exchange membrane fuel cells (PEMFCs), securing sufficient hydration in perfluorosulfonic acid (PFSA) membrane is considered an indicator of performance and durability. Here, we present a straightforward yet effective strategy that sandwiches the nanoporous carbon nanotube (CNT) sheet between the cathodic gas diffusion backing layer (GDBL) and bipolar plate (BP) of a conventional membrane electrode assembly (MEA). CNT sheets are synthesized through the cost-effective direct spinning method. The carbon source, winding rates, and the number of layers are varied to tailor the thickness and nanoporous morphology of the CNT sheets (5, 15, and 30 μm). CNT interlayer MEAs are evaluated for their performance in various temperature and relative humidity (RH), ranges of 80–120 °C and 25–100% RH. With these nanoporous CNT sheets, reactants disperse homogeneously, enhancing membrane hydration and interfacial contact, thereby fulfilling superior performance compared to conventional under entire conditions. Among CNT interlayers, the 30 μm records a 115.4% enhanced peak power density (0.28 W cm −2 ) and 89.2% extended durability (∼187 h) than conventional under 120 °C and 25% RH. Our strategy delivers a broader perspective of PEMFCs and other fuel cell types based on their ease of production and reproducibility. Graphical abstract: Image 1 Highlights: Nanoporous CNT functional interlayers were prepared by direct spinning. CNT interlayer notably boosts the performance of PEFMCs under all test conditions. CNT interlayer also achieves 89.2% extended durability of PEMFCs. These promising boosting mechanisms were demonstrated and optimized.